2020
DOI: 10.1002/ana.25701
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk for Fingolimod, Natalizumab, and Rituximab in Multiple Sclerosis Patients

Abstract: Objective: Novel, highly effective disease-modifying therapies have revolutionized multiple sclerosis (MS) care. However, evidence from large comparative studies on important safety outcomes, such as cancer, is still lacking. Methods: In this nationwide register-based cohort study, we linked data from the Swedish MS register to the Swedish Cancer Register and other national health care and census registers. We included 4,187 first-ever initiations of rituximab, 1,620 of fingolimod, and 1,670 of natalizumab in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 43 publications
4
64
1
Order By: Relevance
“…The rate of malignant cancer in our study was similar to the general population (3.5/1000 PY in general population vs. 4.2/1000 PY) 23 . This is consistent with a nationwide register‐based cohort study conducted in Sweden, which found no difference in the risk of invasive cancer in rituximab‐treated MS patients compared to the general population 24 . MS and NMOSD are associated with an increased risk of non‐superficial thromboembolic events 25,26 .…”
Section: Discussionsupporting
confidence: 86%
“…The rate of malignant cancer in our study was similar to the general population (3.5/1000 PY in general population vs. 4.2/1000 PY) 23 . This is consistent with a nationwide register‐based cohort study conducted in Sweden, which found no difference in the risk of invasive cancer in rituximab‐treated MS patients compared to the general population 24 . MS and NMOSD are associated with an increased risk of non‐superficial thromboembolic events 25,26 .…”
Section: Discussionsupporting
confidence: 86%
“…The overall malignancy rate observed among all ozanimod-treated RMS study participants (289.3/100,000 PY) was similar to those with less exposure in phase 3 trials (298.2/100,000 PY). It was also consistent with reported malignancy rates among MS patients treated with other disease-modifying therapies (IR 290 to 1190/100,000 PY) (Cook et al, 2019) and the rate of invasive cancers in a general Swedish age-matched non-MS population (310/100,000 PY) (Alping et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…A large, long-term analysis based on patient records from 6,883 persons with MS born between 1930 and 1979, who were registered with various Norwegian MS and Cancer Registries, suggests that persons with MS may have a greater overall risk of 14% of developing cancer than the general population, with a higher risk of 66% for cancer in respiratory organs, 51% in urinary organs, and risk of 52% for cancer of the central nervous system compared with the non-MS population (38). A nationwide register-based Swedish study found that the cancer rates were overall similar to the rates among the general population, with no evidence of an increased risk for those treated with rituximab or natalizumab but with a borderline significant increased risk of invasive cancer for patients treated with fingolimod, compared to both the general population and the MS population treated with rituximab (39). A previous Swedish study showed increased mortality risk following a cancer diagnosis among persons with MS compared to those without cancer, but this risk was lower than in the general population with cancer (40).…”
Section: Cancermentioning
confidence: 96%